Development of a real-time PCR method for quantification of Prevotella histicola from the gut. (December 2017) - Balakrishnan, Baskar; Luckey, David; Marietta, Eric; Karau, Melissa; Patel, Robin; Murray, Joseph; Taneja, Veena
Abstract: We designed species-specific primers and developed a qPCR method for enumerating P. histicola from intestinal samples. The two designed primer sets showed specificity for the target 16S rRNA gene of P. histicola . The absolute qPCR method was sensitive to quantify as few as 10 3  colony-forming units (CFU) in the gut. Highlights: Developed an absolute qPCR method for quantifying P. histicola from gut samples. Designed primers for qPCR showed high specificity to16S rDNA gene sequence of P. histicola. Accuracy in quantification achieved by preparing simulated standards from control gut samples.